Himalayan Households, Tamang Demography and Domestic Process - Sapkota, Prakash Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2010)
Thomes E. Fricke 1981, Himalayan Households, Tamang Demography and Domestic Process, Book Faith India, 1993 ( pp 227) Price 300 Rs DOI: 10.3126/dsaj.v3i0.2789 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 201-206